2020
DOI: 10.21203/rs.3.rs-86353/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-phospholipids antibodies and immune complexes in COVID-19 patients: a putative role in disease course for anti-annexin-V antibodies

Abstract: Introduction: Besides distinctive respiratory and digestive hallmarks, COVID-19 has been recently associated with a high prevalence of pro-inflammatory and hypercoagulable states known as “COVID-19 Associated Coagulopathy” (CAC), corresponding to a worsening in patients’ conditions, whose causes are still to be elucidated. A link between anti-phospholipids antibodies (aPLs) and viral infections has long been suggested. APLs are assessed for Anti-phospholipid Syndrome (APS) diagnosis, characterized by thrombocy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
1
1
Order By: Relevance
“…Indeed, we found that, globally, IgM or IgG levels are increased upon infection with SARS-CoV-2, with 66% of individuals having aPL against �1 antigen (non-infected controls: 15%), 40% against �2 antigens (noninfected controls: 0%), and 21.3% against �3 antigens (non-infected controls: 0%), using a threshold of OD � 50. Thus, the prevalence of aPL was higher in our study than previously reported [13,15,50,51,55], despite not including LA in the measurements, and in spite of omitting IgA aPL. Importantly, we detected significant distributional changes between noninfected controls and SARS-CoV-2-infected individuals for IgM aPL against AnV, β2, and PT using Fisher's exact test (p-values < 0.01), and for β2, and PT using Wilcoxon rank sum test (p-values < 0.01 after Benjamini-Hochberg correction).…”
Section: Plos Pathogenscontrasting
confidence: 79%
“…Indeed, we found that, globally, IgM or IgG levels are increased upon infection with SARS-CoV-2, with 66% of individuals having aPL against �1 antigen (non-infected controls: 15%), 40% against �2 antigens (noninfected controls: 0%), and 21.3% against �3 antigens (non-infected controls: 0%), using a threshold of OD � 50. Thus, the prevalence of aPL was higher in our study than previously reported [13,15,50,51,55], despite not including LA in the measurements, and in spite of omitting IgA aPL. Importantly, we detected significant distributional changes between noninfected controls and SARS-CoV-2-infected individuals for IgM aPL against AnV, β2, and PT using Fisher's exact test (p-values < 0.01), and for β2, and PT using Wilcoxon rank sum test (p-values < 0.01 after Benjamini-Hochberg correction).…”
Section: Plos Pathogenscontrasting
confidence: 79%
“…Irrespective, as for the case with LA, 11 there was also a large body of publications related to solid-phase aPL. 31 32 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Although additional relevant papers are likely available in the literature, the captured articles are sufficient for us to critically review the main literature to date. As for LA, 11 there was a wide variety of methods employed to identify solid-phase aPL ( Table 1 ), but sometimes the methodology was not reported.…”
Section: Results Of the Literature Review: Is Apl Present In Covid-19?mentioning
confidence: 99%
“…Platelet‐activating CIC are found in all severely ill COVID‐19 patients but not mild cases. [ 95 , 96 , 97 ] Notably, neither molecular mimicry theory nor bystander theory predicts the formation of CIC. Complementary antibodies will, in turn, target molecularly complementary host antigens of which many examples exist in Tables 1 and 2 .…”
Section: Discussionmentioning
confidence: 99%